A Fluorogenic Far Red-Emitting Molecular Viscometer for Ascertaining Lysosomal Stress in Live Cells and Caenorhabditis elegans - Silswal, Akshay; Kanojiya, Ashutosh; Koner, Apurba Lal (Frontiers in Chemistry, 2022)
The cellular physiochemical properties such as polarity, viscosity, and pH play a critical role in cellular homeostasis. The dynamic change of lysosomal viscosity in live cells associated with different environmental stress remains enigmatic and needs to be explored. We have developed a new class of Julolidine-based molecular viscometers with an extended π-conjugation to probe the lysosomal viscosity in live cells. High biocompatibility, pH tolerance, and the fluorogenic response with far red-emission (>600 nm) properties make these molecular viscometers suitable for live-cell fluorescence imaging in Caenorhabditis elegans. Among these probes, JIND-Mor is specifically designed to target lysosomes via simple modification. The real-time monitoring of lysosomal viscosity change under cellular stress was achieved. We believe that such a class of molecule viscometers has the potential to monitor lysosomal health in pathogenic conditions.